2022
DOI: 10.33225/pec/22.80.179
|View full text |Cite
|
Sign up to set email alerts
|

TEACHING AND LEARNING MECHANICS EXPLORED THROUGH THE USE OF THE 5E’s EDUCATIONAL MODEL

Abstract: This study assesses the level of application of the 5E’s educational model by Rwandan physics teachers and how the model affects the learning of basic classical mechanics in secondary school physics classrooms. For this analysis, quantitative data were collected using the classroom observation tool framed at the 5E’s educational model. A sample of six secondary physics teachers was selected purposively from three boarding secondary schools of Nyamasheke district in the western province of Rwanda to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This research has specifically revealed how inquiry-based learning makes biology more interesting and easier for students to understand biological concepts. This can specifically be seen in the inquiry-based learning method used in an experimental group of students, which is an active learning method that offers a learning environment that facilitates learners to collaborate and actively engage in their learning (Nkurikiyimana et al, 2022;Nyirahagenimana et al, 2022). This study is in agreement with other studies revealing that teaching methods that actively engage learners in biology lesson with resources improve students' attitude toward learning biology (Armbruster et al, 2010;Fančovičová & Prokop, 2008;Kisoglu, 2018;Mukagihana et al, 2021a;.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This research has specifically revealed how inquiry-based learning makes biology more interesting and easier for students to understand biological concepts. This can specifically be seen in the inquiry-based learning method used in an experimental group of students, which is an active learning method that offers a learning environment that facilitates learners to collaborate and actively engage in their learning (Nkurikiyimana et al, 2022;Nyirahagenimana et al, 2022). This study is in agreement with other studies revealing that teaching methods that actively engage learners in biology lesson with resources improve students' attitude toward learning biology (Armbruster et al, 2010;Fančovičová & Prokop, 2008;Kisoglu, 2018;Mukagihana et al, 2021a;.…”
Section: Discussionsupporting
confidence: 82%
“…In pursuance of inquiry-based learning influence on students' attitudes, studies revealed that when students are subjected to inquiry-based instruction, they are more engaged in the lesson (Nkurikiyimana et al, 2022;Sandika & Fitrihidajati, 2018). Interactions between students are more encouraged, and more collaborations while exploring concepts in their respective groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that students learn actively and get interested in computer-based teaching methods (Nzaramyimana et al, 2021). In addition, Nkurikiyimana et al (2022) stressed that students increase their understanding of physics concepts through strong interactive activities and multimedia. Thus, there is a need to study strategies used while teaching quantum physics (Krijtenburg-Lewerissa et al, 2017), where students' perceptions about the teachers' used methods come in.…”
Section: Introductionmentioning
confidence: 99%
“…In Rwanda, secondary school teachers mastered applying adequate interactive teaching approaches whereby they integrate exciting activities, a variety of events, and relevant visualizations that boost learners' confidence to express their ideas and link learning content to real-life experiences (Nyirahagenimana et al, 2022). Indeed, Nkurikiyimana et al (2022) argue that students are motivated and are able to understand physics concepts when strong interactive activities and multimedia are used. However, Ndihokubwayo et al (2020b) found that teachers do not fully exploit the use of PhET simulations and YouTube videos which are likely to sustain students' interest in learning.…”
Section: Introduction 11 Background To the Studymentioning
confidence: 99%